Heparins crossover in percutaneous coronary interventions: a real issue with increasing rate of transradial procedures?. Issue 7 (July 2015) - Sciahbasi, Alessandro; Rigattieri, Stefano; Calcagno, Simone; Mancone, Massimo; Pendenza, Gianluca; Cera, Maria; Danza, Aurora Ilaria; Di Russo, Cristian; Bruno, Pasqualina; Fedele, Silvio; Pugliese, Francesco Rocco; Sardella, Gennaro
Abstract : Aims: Current guidelines give a class III recommendation to the intraprocedural use of unfractionated heparin (UFH) in patients pretreated with enoxaparin. The aim of our study was to evaluate bleeding complications in patients who underwent percutaneous coronary interventions (PCIs) performed using intraprocedural crossover of heparin therapy. Methods: We retrospectively evaluated all PCIs performed at two Italian hospitals since January 2011 to December 2013. After a propensity-matched analysis, patients were divided into two groups (with a ratio 1 : 2) according to intraprocedural crossover of heparins (from enoxaparin to UFH) (Group 1) or intraprocedural UFH alone (Group 2). The primary end-point was a haemoglobin drop of at least 3 g/dl within 48 h after the procedure. Results: During the 3 years analysed, 3224 patients underwent PCI, and after the propensity analysis, 309 patients were considered eligible for our study: 104 patients in Group 1 (69 ± 12 years, 78% men) and 205 patients in Group 2 (69 ± 13 years, 80% men, P = NS). There were no significant differences between the two groups for BMI, periprocedural use of antiplatelet therapy, baseline haemoglobin haematocrit or platelets levels. The primary end-point did not differ between the two groups (2.9% in Group 1 and 3.4% in Group 2, P = 0.550). Also, nadir of haematocrit or haemoglobin levels did not differ between the two groups. Finally, in hospital, major adverse cardio-cerebrovascular events did not differ between the two groups (1.9% in Group 1 and 3.9% in Group 2, P = 0.50). Conclusion: In this retrospective analysis of a large PCI database, the 'heparins crossover' during PCI was not associated with increased bleeding risk.